Energy Minimization for In-Band Full-Duplex Relaying Using an Amplify-and-Forward UAV Relay - Ji, Xiaodong; Wang, Tao; Shi, Senyi; Gu, Jian-Feng (Vehicular Communications, 2024)
This paper investigates an in-band full-duplex (IBFD) relaying, where a fixed-wing unmanned aerial vehicle (UAV) is dispatched as an amplify-and-forward relay to forward data from a source to a destination. By considering ideal and practical IBFD cases, new received signal-to-noise ratio (SNR) expressions at the destination are derived. Armed with the newly derived SNR expressions and the existing one in literature, three different lower-bounds of the size of data received by the destination are calculated. Using the three lower-bounds of the size of data, an optimization problem corresponding to energy minimization of the IBFD relaying system subject to a total data-bit constraint in addition to a mission completion time (MCT) constraint is solved, leading to three sets of solutions. Computer simulation experiments are conducted and the accuracy of the derived SNR expressions and the three sets of solutions of the optimization problem are compared. The results demonstrated that the newly derived SNR expressions are more accurate than the existing one in literature and are more suitable to be utilized for energy minimization, and the proposed optimization method can complete the relaying task with the minimum energy and MCT. When the residual loop-interference channel power is equal to -100dB, the scheme of ideal IBFD only consumes up to 2.5% of the energy of the compared schemes regardless of the value of the total data-bit constraint.